PRODUK MAKANAN DAN MINUMAN YANG TIDAK BISA DISERTIFIKASI HALAL OLEH MAJELIS ULAMA INDONESIA PERSFEKTIF MASLAHAH DALAM ETIKA BISNIS ISLAM - Triana Apriani; Rahmat Aji Nuryakin (JURNAL AGHNIYA, 2022)
Abstract The halal aspect of a product is an obligation for Muslim consumers. Along with the development of technology and information as well as the creative economy industry, one of them is in the culinary sector. Certification and labeling of halal products provides protection, assurance, and information about the halalness of products consumed by the public. The purpose of this study is to add scientific insight into the reasons for food and beverage products, which in terms of ingredients and production processes used have no problems in the aspect of halalness but cannot be certified as halal by LPPOM MUI and what is the perspective maslahat on Islamic business ethics. This study uses a qualitative descriptive research method with a juridical-normative approach. The results of the study concluded that the MUI halal certification mechanism for food and beverage products that are halal in substance but cannot be certified according to the Decree of the LPPOM MUI Number SK46 / Dir / LPPOM MUI / XII / 14 in the perspective of Islamic business ethics.Keywords:Food and Beverages, Halal Certificate, Islamic Business Ethics AbstrakAspek halal suatu produk merupakan kewajiban bagi konsumen umat muslim. Seiring dengan perkembangan teknologi dan informasi serta industri ekonomi kreatif salah satunya di sektor kuliner. Sertifikasi dan labelisasi produk halal memberikan perlindungan, jaminan, serta informasi tentang kehalalan produk yang dikonsumsi masyarakat. Tujuan dari penelitian ini agar menambah wawasan ilmiah mengenai alasan produk makanan dan minuman yang dari sisi bahan maupun proses produksi yang dipergunakan tidak ada masalah dalam aspek kehalalan namun tidak bisa disertifikasi halal oleh LPPOM MUI dan bagaimana persfektif maslahat dalam etika bisnis islam. Penelitian ini menggunakan metode penelitian deskriftif kualitatif dengan pendekatan yuridis-normatif. Hasil penelitian disimpulkan bahwa mekanisme sertfikasi halal MUI pada produk makanan dan minuman yang halal secara zat namun tidak bisa disertifikasi sesuai Surat Keputusan LPPOM MUI Nomor SK46/Dir/LPPOM MUI/XII/14 dalam persfektif etika bisnis islam.Kata Kunci:Produk Makanan, Sertifikat Halal, Etika Bisnis Islam